An atlas of histology - Zhang, Shu-Xin (New York Springer-Verlag, 1999)
Bridging the gap between textbook diagrams and the complex reality of histrological preparations, this magnificent atlas of human micro anatomy is designed to help students understand the complex structures encountered when viewing microscopic sections of tissues. Instead of simply depicting an individual section, each drawing is a compilation of the key structures and features seen in many preparations from similar tissues or organs. Invaluable to students in a range of life science and medical disciplines including human and veterinary medicine, dentistry, mammalian biology, pharmacy, and nursing.
Keywords: Histrology -- Atlases; Histology -- Medicine -- Cytology; Human anatomy -- Human physiology